PERLINDUNGAN HAK-HAK TERSANGKA KORUPSI PADA TAHAP PENYIDIKAN DAN PENUNTUTAN OLEH KOMISI PEMBERANTASAN KORUPSI - Wiryawan, Palupi (Tadulako Master Law Journal, 2020)
The Criminal Procedure Code has provided a dimension of protection for human rights in its balance with the public interest, especially in the protection of the rights of suspects or defendants in investigation and prosecution process. However, it cannot be denied that the law enforcers neglected the rights of suspects, defendants and witnesses. The purpose of creating this thesis was for learning and analyzing the protection of the rights of corruption suspects and defendants in investigations and prosecutions by the Corruption Eradication Commission also what efforts can be made by the corruption suspects and defendants.The research method that was used in this thesis was juridical normative. The research’s specification was perspective analysis. The method of compiling data was by secondary files from library studies.Based on the result of the research, it was found that to carry out its duties, the Investigator and Public Prosecutor in the Corruption Eradication Commission not only applied the Corruption Eradication Commission Act but also must apply the Criminal Procedure Code (KUHAP) especially in the provisions of Article 50 Paragraph (1) and Paragraph (2), that was the suspect has the right to immediately get an examination by the investigator so that it can be submitted to the public prosecutor and immediately tried by the court to shorten the process of resolving his criminal case. Corruption suspects that were investigated and prosecuted by the Corruption Eradication Commission could make legal efforts through pretrial justice, justice collaborators, claimed for rehabilitation and compensation also there was a time limit in the judicial process so that the principle of fast and light costs judicial especially legal certainty can be achieved.